صورة ماساة حلبجة باسلوبين مختلفين بين بلند الحيدري ومحمود البريكان - علي، طاهر مصطفى (جامعة صلاح الدين, 2016)
يتضمن هذا البحث دراسة أسلوبية تقابلية عن أسلوب الشاعرين بلند الحيدري ومحمود البريكان في تصويريهما الشعريين لمأساة حلبجة الشهيدة، على صعيد الأسلوب والبناء وكذلك المثير الموضوعي للتجربة بغية تقديم خدمة معرفية أكاديمية في المجال النقدي وكذلك خدمة ثقافية للقضية والموضوع، من خلال مقدمة وثلاثة محاور دراسية تعقبها خاتمة ومصادر وخلاصتان.
This research is a stylistic one between two Iraqi poets: Blind Haydari and Mahmoud Brikan. It is about poetic portrayal about Halabja catastrophe. This research is constructed in three sections, the first section is about analyzing subject semiologically which is manipulated and portrayed by Brikan, the second one is concerned with process of analysis in structure and simplicity, the third one present’s stylistic procedure activity in Haydari and cinematic view by Brikan. The research results in points of results and conclusions followed by list of references.
Keywords: الشعر العربي -- الشعراء العرب -- نقد الشعر -- الدواوين والقصائد -- الأسلوب الادبي